A study on the factors influencing parents decision in choosing private schools : a case study of Selangor - Noor Alyani binti Yaacob (Kulliyyah of Architecture and Environmental Design, Internatioal Islamic University Malaysia, 2015)
Current perspectives highlight the importance of educational sector in designing the socio-economic development of a country. It accelerates the economic growth through knowledge and skills development by improving human capabilities. Education is also perceived as an economic commodity. During the last few decades, private schools in Malaysia have emerged as an essential source of imparting education at various levels (Proap & Rihed, 1995). Private schools received financing in part or as a whole from tuition fees, fundraising, and alumni contribution. Providing the children with the most excellent educational atmosphere is parents' desirable wish. Their choice to invest in their children's education is based on a few numbers of factors; social, economic and cultural factors. The research emphasizes on analysing parents' motivation and factors in selecting private school for their children. It aims at investigating factors that influenced parents' decision when selecting private schools for their children. Three problem statements emphasized which are; Planning or development of private schools are not in the Local Plan (LP), Physical development of facilities provided does not adhere to school development guidelines and Social Exclusion. The objectives of the research are to study the development of private schools in Selangor, to identify the factors influencing parents' decision in selecting private schools over public schools, to assess the physical condition of the selected private schools based on Manual Guidelines of Town and Country Planning Department and/or School Infrastructure requirement by the Ministry of Education, and to provide suggestions and recommendations in enhancing the development of private schools within the study area. The data for this research were collected through site observation of physical conditions and facilities of participating private schools, questionnaire survey of 510 respondents among parents and interview sessions with the administrators and parents to validate the findings from site observation and questionnaire survey. The state of Selangor is selected to represent the overall states in Malaysia due to the presence of many esteemed and established private institutions. Based on the study, the potential relationship of Social Background/Status, Income Level, School Syllabus, School Environment/Facilities, School Performances, Location, Teacher Quality and Distance were analysed. Using the Relative Important Index (RII), it was found that the parents ranked factors as stated; school syllabus, school environment, school performances, teacher quality, location, distance, social background and income level. The recommendations for the study is to provide a specific guidelines as well as proper land use provision for private educational institution in land use planning and highlighted the important of private schools in providing alternative, variety and specialist education other than offered by normal public schools in Malaysia. The study also acknowledge that the provision of proper and adequate facilities and formulation of a detailed and inclusive private school environment to all children.